Sugar production from bioenergy sorghum by using pilot scale continuous hydrothermal pretreatment combined with disk refining. (October 2019) - Cheng, Ming-Hsun; Dien, Bruce S.; Lee, D.K.; Singh, Vijay
Highlights: The continuous pretreatment was scaled up from 40 ml hot water pretreatment. Disk refining has synergistic effect on improving sugar yields. The optimal sugar yields were obtained from pretreatment severity of 3.65. No furans were detected in enzymatic hydrolysates. The continuous pretreatment increased surface area due to a steam explosion step. Abstract: Chemical-free pretreatments are attracting increased interest because they generate less inhibitor in hydrolysates. In this study, pilot-scaled continuous hydrothermal (PCH) pretreatment followed by disk refining was evaluated and compared to laboratory-scale batch hot water (LHW) pretreatment. Bioenergy sorghum bagasse (BSB) was pretreated at 160–190 °C for 10 min with and without subsequent disk milling. Hydrothermal pretreatment and disk milling synergistically improved glucose and xylose release by 10–20% compared to hydrothermal pretreatment alone. Maximum yields of glucose and xylose of 82.55% and 70.78%, respectively were achieved, when BSB was pretreated at 190 °C and 180 °C followed by disk milling. LHW pretreated BSB had 5–15% higher sugar yields compared to PCH for all pretreatment conditions. The surface area improvement was also performed. PCH pretreatment combined with disk milling increased BSB surface area by 31.80–106.93%, which was greater than observed using LHW pretreatment.